Budget Template for Home Canning - Kevin Athearn; Amarat Simonne; Soohyoun Ahn (EDIS)
One in five US households cans fruits or vegetables in a home kitchen. If your household is one of them, you may want to know the full cost of the activity or how much money you are saving by doing it yourself. This 10-page fact sheet written by Kevin R. Athearn, Amarat Simonne, and Soohyoun Ahn and published by the UF/IFAS Food and Resource Economics Department presents a template designed to assist you in estimating the cost and potential returns from canning food at home. http://edis.ifas.ufl.edu/fe1034